Greenhouse gas emission due to forest fires in three tree communities in Michoacán - Ortiz-Mendoza, Ruben; González-Tagle, Marco Aurelio; Pérez-Salicrup, Diego Rafael; Aguirre-Calderón, Oscar Alberto; Himmelsbach, Wibke; Cuéllar-Rodríguez, Luis Gerardo (Ecosistemas y Recursos Agropecuarios, 2025)
The forest fires consume large amounts of forest fuel and emit greenhouse gases into the atmosphere, mainly CO2 and CO. The objective of this work was to calculate the emission from burning of the litter layer, and to calculate the emissions considering all vegetation strata in the Mariposa Monarch Biosphere Reserve to Indicate If the arboreal community correspond or not to same fuelbeds. For this purpose, the litter layer in arboreal community the oyamel, pine-oyamel and pine-oak was burned. The CONSUME program was used to calculate emissions of all the strata. It was obtained that the litter layer with the lowest total emissions corresponded to fir with 46 g kg-1 compared to 647, and 437 g kg-1 recorded in pine-fir and pine-oak, respectively (p< 0.05). Emission prediction models were obtained for CO2, CO, CH4, NO2 and NOX, which explained 74% of the emissions generated from burning. With CONSUME, the oyamel community obtained higher emissions. The emission presented a correlation of 85% with consumption, with 43% higher consumption in low humidity fuels compared to high humidity fuels. Communities composed of pine did not show any variation in emissions, the high fuel load influences a high emission from a fire, so that a higher emission from a fire can be expected.
Keywords: Fire behavior; estimation equations; combustion efficiency factor; combustion phases; burning of needles